Development of a Social Value Framework Based on Strategic Management with a Stakeholder Theory Approach Using Qualitative Thematic Analysis - Abedi, Amirhossein; Ebrahimi Kahrizsangi, Khadijeh; Molaei , Mahnam (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective:  The objective of this study was to develop and conceptualize an integrated framework for social value grounded in strategic management principles through the lens of stakeholder theory.Methods and Materials: This research was conducted as an exploratory qualitative study within an interpretive paradigm using thematic analysis as the primary methodological approach. The study population consisted of academic and professional experts in accounting, financial reporting, sustainability standards, and corporate governance, selected through purposive and snowball sampling. Data were collected through documentary analysis of relevant scholarly texts and semi-structured interviews with fourteen experts until theoretical saturation was achieved. Interviews were audio-recorded, transcribed verbatim, and analyzed following the systematic procedure of thematic analysis and thematic network construction. Trustworthiness was ensured through prolonged engagement, member clarification during interviews, researcher triangulation, and inter-coder agreement assessment. The analysis aimed to identify patterns of meaning leading to the extraction of basic, organizing, and global themes forming the conceptual structure of the proposed framework.Findings: The inferential analysis revealed a coherent multidimensional structure of social value consisting of three interrelated global themes: strategic requirements of social value, social value perception, and social value implementation structures. These dimensions collectively demonstrate that social value operates as a strategic organizational capability rather than a peripheral ethical activity. The findings indicate that effective integration of social value depends on alignment between strategic decision-making, stakeholder management mechanisms, performance perception processes, and organizational execution systems. The thematic relationships further suggest that organizations generate sustainable social value when governance structures, performance evaluation practices, and resource allocation mechanisms are systematically aligned with stakeholder expectations and long-term strategic objectives.Conclusion: The study concludes that embedding social value within strategic management requires a holistic organizational architecture that integrates stakeholder engagement, strategic governance, perception management, and operational execution mechanisms. The proposed framework offers a theoretically grounded and practically applicable model for transforming social value from a normative concept into an institutionalized strategic process capable of enhancing organizational legitimacy, sustainability performance, and stakeholder trust.